KAJIAN TENTANG KAIN ADAT TENUN KOLANA BERDASARKAN MOTIF DAN WARNA DI KECAMATAN ALOR TIMUR - Novi Greace Makena; Paulus Ayub Animau, Mita Lodia Sing, Ria Bolang, Penina Maruli, Halena M. Bekata, Petrus Mau Tellu D (Adiba Aisha Amira, 2025)
This study aims to explore the motifs of woven fabrics that developed in Kolana Utara Village, Alor Timur District, Alor Regency, focusing on the cultural symbolism and local identity contained in the design. Woven fabrics in this region have distinctive characteristics that reflect the cultural wealth of the local community, which is not only influenced by aesthetic factors, but also traditional values and deep history. Through an ethnographic approach, this study identifies the various motifs used in northern kolana woven fabrics and analyses the symbolic meaning behind each motif, as well as its relation to the social life and beliefs of the community. Data collection techniques used interviews, interviews conducted with community leaders. Based on interviews, the results showed that woven fabrics in the northern kolana village function as a medium to express local identity, strengthen social cohesion, and maintain a valuable cultural heritage. Thus, this woven fabric is not only a craft product, but also a symbol of the sustainability and identity of the north kolana community.